HEALTH COMMUNICATION LITERACY OF ADOLESCENT REPRODUCTIVE SYSTEM IN BANTUL REGENCY YOGYAKARTA - Mochammad Fauzul Haq; Muhammad Muhajir (The Indonesian Journal of Communication Studies, 2020)
The phenomenon of early marriage in Indonesia seems to be shared. Indonesia is the second-highest country in ASEAN in the level of early marriage. Bantul Regency, as part of the Special Region of Yogyakarta Province, faces a similar problem, early marriage rates are relatively high. This is crucial because early marriage is vulnerable to various problems, including physical and mental health problems. This research focuses on the level of youth literacy in the Banguntapan village, Bantul Regency, about sex education. Besides, this research also focuses on health communication by the government to educate adolescents related to sex education. The design of this study is qualitative, data collection techniques carried out with Content Analysis, In-Depth Interview, and Focused Group Discussion. The data analysis technique used is a cross-site analysis. The validity test in this study uses source triangulation and method triangulation. The results showed that the literacy culture of adolescents in Banguntapan village is still low; adolescents cannot yet understand sex education. Even so, the government has conducted health communication that focuses on the dangers and effects of sexual relations at an early age.